Age, growth and maturity for two highly targeted jack species: Caranx ignobilis and Caranx melampygus. Issue 4 (4th July 2021) - Pardee, Cassandra; Wiley, John; Springer, Sarah
Abstract: This study provides growth rate, longevity and maturity estimates for the two important species of jack in Hawaiʻi: ulua aukea/giant trevally Caranx ignobilis and omilu/bluefin trevally Caranx melampygus . Maximum observed ages for C. ignobilis and C. melampygus were 31 years and 24 years, respectively. Combined sex von Bertalanffy growth parameter values for C. ignobilis and C. melampygus were as follows: L ∞ = 1064 mm and K = 0.18 year −1 ; and L ∞ = 718 mm and K = 0.20 year −1, respectively. Female size at maturity was significantly greater than males for both C. ignobilis and C. melampygus . Size and age at maturity for C. ignobilis was 594 mm and 4.4 years for females and 465 mm and 2.8 years for males. Size and age at maturity for C. melampygus was 372 mm and 4.1 years for females and 329 mm and 2.9 years for males. This study provides the first robust demographic data for both of these highly prized and ecologically important predatory species in Hawaiʻi, which can be used for future assessments or management.